2019
DOI: 10.1186/s41180-018-0022-2
|View full text |Cite
|
Sign up to set email alerts
|

Examination of sustainability reporting practices in Indian banking sector

Abstract: Sustainability reporting is at the core of designing corporate sustainability environment. The study has been conducted on Indian banking sector to examine the extent of sustainability reporting by the banks operating in India. Sustainability report, corporate social responsibility report, business responsibility report and annual report (FY 2015-16 & 2016-17) of the banks were analysed and coded using content analysis technique against sustainability indicators derived from review of literature, GRI G4 guidel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
51
1
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(76 citation statements)
references
References 53 publications
3
51
1
1
Order By: Relevance
“…Thus, if we use this lexical analysis to understand whether these financial services SMEs properly developed their sustainability reporting, the obtained results show that although they used some specific words to meet the minimum requirements, the financial dimension of reporting continues to be more important, and the other information is used to increase the length of the report but still does not reflect significant environmental and social impacts. According to previous studies [75], sustainability reporting in financial companies has as the highest priorities those directly related to their business operations.…”
mentioning
confidence: 99%
“…Thus, if we use this lexical analysis to understand whether these financial services SMEs properly developed their sustainability reporting, the obtained results show that although they used some specific words to meet the minimum requirements, the financial dimension of reporting continues to be more important, and the other information is used to increase the length of the report but still does not reflect significant environmental and social impacts. According to previous studies [75], sustainability reporting in financial companies has as the highest priorities those directly related to their business operations.…”
mentioning
confidence: 99%
“…Indian CSR reports have often contained little related to environmental issues [37,177,192]. Even a recent study of the banking sector in India found the disclosure of sustainability considerations still in a "nascent" stage" [114] (p. 13). This research found that, over a fifteen-year period, each of the corporations from the agrochemical industry studied-subsidiary companies operating in India, their parent companies, and domestic Indian companies-had significant changes in the character of their CED.…”
Section: Discussionmentioning
confidence: 99%
“…The CED studies differ substantially in the focus of the research and in their approaches and methods. Unlike some of the studies of the broader CSR research that investigated a specific industrial sector (e.g., [112][113][114]), they each investigated companies across multiple sectors. Half of the studies were empirical in nature (i.e., theories may be mentioned but do not form the basis of either method or discussion).…”
Section: Corporate Environmental Disclosure In Indiamentioning
confidence: 99%
“…Research aims to examine the extent of environmental performance reporting and compare the association amid environmental performance and financial performance on a sample of 21 financial sector [45]. Content analysis which has been extensively utilized in the extant literature has been employed in this research to determine environmental disclosure score [46].…”
Section: A Data and Variablesmentioning
confidence: 99%
“…Hypothesis 4: There is a significant association between environmental performance and return on equity of public sector banks operating in India. [45]. Involvement of banks towards environmental activities and its reporting is still in its preliminary phases.…”
Section: B Hypothesis Framedmentioning
confidence: 99%